Acidic or Alkaline? Towards a New Perspective on the Efficiency of Water Electrolysis. Issue 11 (1st January 2016) - Schalenbach, Maximilian; Tjarks, Geert; Carmo, Marcelo; Lueke, Wiebke; Mueller, Martin; Stolten, Detlef
Abstract : Water electrolysis is a promising technology for enabling the storage of surplus electricity produced by intermittent renewable power sources in the form of hydrogen. At the core of this technology is the electrolyte, and whether this is acidic or alkaline affects the reaction mechanisms, gas purities and is of significant importance for the stability and activity of the electrocatalysts. This article presents a simple but precise physical model to describe the voltage-current characteristic, heat balance, gas crossover and cell efficiency of water electrolyzers. State-of-the-art water electrolysis cells with acidic and alkaline electrolyte are experimentally characterized in order to parameterize the model. A rigorous comparison shows that alkaline water electrolyzers with Ni-based catalysts but thinner separators than those typically used is expected be more efficient than acidic water electrolysis with Ir and Pt based catalysts. This performance difference was attributed mainly to a similar conductivity but approximately 38-fold higher diffusivities of hydrogen and oxygen in the acidic polymer electrolyte membrane (Nafion) than those in the alkaline separator (Zirfon filled with a 30 wt